Knowledge, Attitude and Practice of Epileptic Patients Towards Their Disease - Syeda Shumaila Fatima, Shahnaz Shah, Jaysingh, Abu Bakar Shaikh, Sameena Majeed, Muhammad Munwar Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Epilepsy is a persistent brain condition. Patients with this condition experience repeated seizures that are brought on by unexpected, abrupt, and excessive electrical discharges in the brain cells. Numerous morbidities, including death and lowered quality of life, are linked to epilepsy (QoL). The development of the proper attitude toward the disease was aided by epilepsy sufferers’ awareness of their condition. Objective: To determine the frequency of adequate knowledge of patients who present with epilepsy at neurology ward of tertiary care hospital in Karachi. The design of this study was descriptive cross-sectional study. This study was conducted at Jinnah Postgraduate Medical Centre, Karachi and the duration of this study six months and was from January 2021 to June 2021. A total of 91 diagnosed case of epilepsy were included in this study. The researcher was collected data on a prescribed questionnaire regarding demographic variables like age, gender, education level, profession, monthly family income, address & duration of disease. All questions to measure the knowledge, attitude & practices were closed ended with the answer ending in fixed options (Yes/ No). Each correct answer was given score 01and summed up. Results: The mean age of the patients was 43.08±10.88 years. There were 42(46015%) male and 49(53.85%) female. Frequency adequate knowledge of patients who present with epilepsy was observed in 24.18% (22/91) cases. Conclusion: The patients in our research had a rudimentary awareness of epilepsy, but they had little information about safety precautions, social concerns, or available treatments. In order to enhance AKA for epileptic patients and their families, an improved public epilepsy education paradigm, such as an IT-based epilepsy education tool, is certainly required given the existing level of patient knowledge of the condition. These knowledge gaps between the patient and caregiver might be identified by medical specialists like doctors and clinical pharmacists. Keywords: Epilepsy, Neurology, Quality Of life, Chronic Brain Disorder